PENGARUH KONSELING TERHADAP SELF STIGMA PASIEN HIV/AIDS DENGAN PENDEKATAN TEORI LAWRENCE GREEN - Imam Ajib Ispurnawan; Noer Saudah; Imam Zainuri (Universitas Pesantren Tinggi Darul Ulum, 2021)
Abstract The stigma that occurs in society against people with HIV and AIDS has an impact on sufferers to stigmatize themselves (Self Stigma). Negative self-acceptance which causes a decrease in self-esteem and self-efficacy so that it affects the individual's belief to be able to recover. The purpose of this study was to analyze the effect of counseling on self-stigma of patients with the Lawrence green theory approach. The research design was a pretest-posttest control group design with a sample size of 40 respondents selected by purposive sampling technique. The instrument used is a questionnaire. Counseling treatment of respondents using the module. The statistical tests used were paired t-test and independent t-test. The test results showed that the treatment group was 0.000 and the control group was 0.104. Correlation coefficient 0.600. The independent t test value of 0.001 means that there is a difference in the average number of self-stigma in the treatment group and the average in the control group after counseling. Counseling with Lawrence Green's theoretical approach can reduce self-stigma so that HIV/AIDS patients think positively about themselves, do not withdraw from the environment and are willing to behave in therapy for their own healing. Keywords: self stigma, HIV/AIDS, counseling, lawrence green